2022
DOI: 10.3390/antiox11091780
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing the Therapeutic Potential of the Nrf2/Bach1 Signaling Pathway in Parkinson’s Disease

Abstract: Parkinson’s disease (PD) is the second most common neurodegenerative movement disorder characterized by a progressive loss of dopaminergic neurons in the substantia nigra pars compacta. Although a complex interplay of multiple environmental and genetic factors has been implicated, the etiology of neuronal death in PD remains unresolved. Various mechanisms of neuronal degeneration in PD have been proposed, including oxidative stress, mitochondrial dysfunction, neuroinflammation, α-synuclein proteostasis, disrup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 256 publications
0
10
0
Order By: Relevance
“…Considering that the main difference between the Keap1–Nrf2 ETGE interaction and the Keap1–Nrf2 DLGex interaction lies in the P6 subpocket, highlighting the P6 subpocket in drug design might hold enormous promise for the development of Keap1–Nrf2 inhibitors with better selectivity. , In addition, targeting the β-TrCP–Nrf2 pathway has been considered as an unexplored alternative to develop Nrf2 activators with higher target selectivity. ,, Recently, the first β-TrCP - Nrf2 PPI inhibitor has been successfully discovered, which represents a new direction for the future exploitation of safe and potent Nrf2 activators . Mounting evidence suggests that pharmacologic inhibition of BTB and CNC homology 1 (Bach1), a physiological repressor of Nrf2, also represents a promising approach to activate the Nrf2–ARE pathway without involving the electrophilic modification of cellular proteins. , In this regard, BACH1 inhibitors have opened the door for a new class of nonelectrophilic Nrf2 activators. , It is noteworthy that glycogen synthase kinase-3β (GSK-3β) can phosphorylate Nrf2, stimulating its association with β-TrCP and precipitating Nrf2 ubiquitination. , Therefore, GSK-3β inhibitors offer additional ways to activate Nrf2 without electrophilicity concerns. More attention should be devoted to these areas. Furthermore, Nrf2 hyperactivation has been reported to be tightly related to the development of some other diseases, including but not limited to cancers, bone hypoplasia, hydronephrosis, and aging acceleration .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that the main difference between the Keap1–Nrf2 ETGE interaction and the Keap1–Nrf2 DLGex interaction lies in the P6 subpocket, highlighting the P6 subpocket in drug design might hold enormous promise for the development of Keap1–Nrf2 inhibitors with better selectivity. , In addition, targeting the β-TrCP–Nrf2 pathway has been considered as an unexplored alternative to develop Nrf2 activators with higher target selectivity. ,, Recently, the first β-TrCP - Nrf2 PPI inhibitor has been successfully discovered, which represents a new direction for the future exploitation of safe and potent Nrf2 activators . Mounting evidence suggests that pharmacologic inhibition of BTB and CNC homology 1 (Bach1), a physiological repressor of Nrf2, also represents a promising approach to activate the Nrf2–ARE pathway without involving the electrophilic modification of cellular proteins. , In this regard, BACH1 inhibitors have opened the door for a new class of nonelectrophilic Nrf2 activators. , It is noteworthy that glycogen synthase kinase-3β (GSK-3β) can phosphorylate Nrf2, stimulating its association with β-TrCP and precipitating Nrf2 ubiquitination. , Therefore, GSK-3β inhibitors offer additional ways to activate Nrf2 without electrophilicity concerns. More attention should be devoted to these areas. Furthermore, Nrf2 hyperactivation has been reported to be tightly related to the development of some other diseases, including but not limited to cancers, bone hypoplasia, hydronephrosis, and aging acceleration .…”
Section: Discussionmentioning
confidence: 99%
“…145 Mounting evidence suggests that pharmacologic inhibition of BTB and CNC homology 1 (Bach1), a physiological repressor of Nrf2, also represents a promising approach to activate the Nrf2−ARE pathway without involving the electrophilic modification of cellular proteins. 146,147 In this regard, BACH1 inhibitors have opened the door for a new class of nonelectrophilic Nrf2 activators. 148,149 It is noteworthy that glycogen synthase kinase-3β (GSK-3β) can phosphorylate Nrf2, stimulating its association with β-TrCP and precipitating Nrf2 ubiquitination.…”
Section: Discussionmentioning
confidence: 99%
“…Basally activated in almost all cellular types, autophagy is particularly important in the survival of cancer cells that are forced to live in condition of shortage of oxygen and nutrients [7]. Moreover, the activation of NRF2 is regulated, through a feed-back mechanism, by Batch1, a transcriptional repressor of NRF2 activated by NRF2 itself [8].…”
Section: Nrf2mentioning
confidence: 99%
“…However, the Nrf2-driven program has a feedback regulation through the transcriptional repressor Bric-a-brac-Tramtrack-Broad (BTB) and cap "n" collar (CNC) homolog 1 (Bach1), which is an Nrf2 target gene and inhibits transcription of a large number of both Nrf2-dependent and Nrf2independent genes. [39,40] Thus, Bach1 activation and inhibition processes are directly implicated in ferroptosis. [41] A recent study showed that Bach1 ablation can protect against ferroptosis in a myocardial infarction model.…”
Section: Nrf2 Target Genes Are Modulators Of Ferroptosismentioning
confidence: 99%
“…There is a clear understanding that Nrf2 activation and Bach1 inhibition properties in one drug make a “mutually beneficial” combination for treating neurodegenerative disorders with perturbed Nrf2/Bach1 signaling. [ 40,52 ]…”
Section: Introductionmentioning
confidence: 99%